0719 The Risk Of Progression Of Chronic Kidney Failure In Patients With Obstructive Sleep Apnea. (25th May 2022) - Salman, Salam; Chovatiya, Jasmine; Justice, Brittney; Holley, Dallin; Verplancke, Kiana; Kerr, Christian; Walters, Ryan; Ng, Ian; Nazmul, mohammed
Abstract: Introduction: To describe the risks of chronic kidney disease (CKD) progression in patients with obstructive sleep apnea (OSA) Methods: In this retrospective case control study; patients with CKD and OSA compared to patients with CKD without OSA who followed up at Creighton University Hospital Clinic. Data retrieved from Electronic Medical Records: demographics, time of diagnosis severity of OSA, apnea hypopnea index, severity of chronic kidney disease using serum creatinine and CKD -EPI equation for glomerular filtration rate cut offs. Patient's kidney function was followed up for 10 years from their diagnosis of OSA. Worsening kidney function is defined on the basis of laboratory values including estimaed GFR( eGFR) and serum creatinine as well as Kidney Diseases Outcome Quality Initiative (KDOQI) 2002 definition and staging. We calculated the mean and SD when appropriate. P values less than 0.05 were considered statistically significant. Results: 269 patients without OSA included in the study. 416 patients with mild OSA, 343 with moderate OSA and 225 with severe OSA mean (SD) age 46.6 (16.3), 52.9(13.5), 56.9(14.1) and 55.3(15.1) years respectively; 59.1, 56.5, 39.1 and 35.6% were females respectively. CKD stage 1 42.8, 26.9, 26.5 and 28.9% respectively. Stage 246.5, 56.3, 54.2 and 46.7% respectively. Stage 3 10.7, 16.9, 19.2 and 24.3% respectivelyPatient's renal functions who had CKD stage 2 or 3 with mild., moderate and severe OSA got worse in 21.2, 31.5 and 26.7% respectively. compared to 13.1% with no sleep apnea.(p <.001)), There was no significant difference on progression of CKD in late stages( CKD IV/V) Conclusion: Patients with OSA and CKD are more likely to have worsening renal function compared to patients without OSA and this association may depend on severity of both CKD and OSA. Support (If Any):